APPLICATION OF HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR QUANTITATIVE ANALYSIS OF GLYCYRRHIZIC ACID IN THE COMPOSITION OF DRY EXTRACT “FLEGMEN” - Matazimov M.T.; Sidametova Z.E; Olimov N.K; Abdullaeva M.U; Khamidullaev Sh.A (Western European Studies, 2024)
The results of determining the amount of glycyrrhizin acid in the dry extract “ Flegmen ” using high-performance liquid chromatography are presented. The composition of the dry extract " Flegmen " includes local plants - Regel's Zopnik ( Phlomisregelii M.Pop . ), Turkestan motherwort ( LeonurusturkestanicusL. ), peppermint ( Menhtapiperita L. ), naked licorice ( Glycyrrhizaglabra L.). According to pharmacopoeial article No. 42 uz-0979-2022, the biologically active substance - glycerrisin in the dry extract " Flegmen " was analyzed by highperformance liquid chromatography. It has been established that its content in 1 g of dry extract is 1.39% and corresponds to the indicator specified in the regulatory document - not less than 1%.
Keywords: dry extract; glycyrrhizin; acid; Flegmen